Issues in the theory of international tax coordination - Peter Birch Sörensen (Bank of Finland, 1990)
This paper surveys the theory ofinternational tax coordination. The first part of the paper discusses the optimal method of international double taxation relief from an equity and efficiency perspective. The second part surveys the modern game-theoretic approach to tax coordination, stressing the potential welfare gains from international cooperation in the field of tax policy. Finally, the third part of the paper reviews the theory of international coordination of indirect taxation.
URN:NBN:fi:bof-201807311791
Keywords: 330